Biological control of gastrointestinal nematodes in horses fed with grass in association with nematophagus fungi Duddingtonia flagrans and Pochonia chlamydosporia - Alves do Carmo, Tábata [UNESP]; Oliveira Mena, Mateus [UNESP]; de Almeida Cipriano, Isabela [UNESP]; Mascoli de Favare, Giordani [UNESP]; Jabismar Guelpa, Gabriel [UNESP]; da Costa Pinto, Sara [UNESP]; Francisco Talamini do Amarante, Alessandro [UNESP]; Víctor de Araújo, Jackson; Velludo Gomes de Soutello, Ricardo [UNESP] (Elsevier, 2023)
Biological control with nematophagous fungi can be used to reduce populations of intestinal parasites, since these are their natural antagonists, minimizing the use of chemical anthelmintics. Therefore, the objective of the present work was to evaluate the combined effect of two nematophagous fungi Duddingtonia flagrans and Pochonia chlamydosporia in the biological control of gastrointestinal helminthoses in horses kept on pasture. Thirty six mares were divided into three groups, one control and two trated, for twelve months. As for the group of animals treated with fungi, inwhich animals in which the animals received a dose of 1 g of formulation containing 105 chlamydospores of D. flagrans and 105 chlamydospores of P. chlamydosporia per gram of the commercial product for each 10 kg of body weight, per day. The group Abamectin, with the animals being treated every 3 months with the anthelmintic 1% abamectin, at a dose of 0.2 mg/kg, administered orally. The proceeding of all treatments was evaluated based on the count of eggs per gram of faeces (EPG) with samples of faeces collected every 28 days and preparation of fecal cultures to identify the different genera of infective larvae, count of infective larvae retrieved from the pasture and microbiological analysis of the faeces. The data were submitted for analysis of variance and means were compared by Tukey's test (5%). The overall average of EPG in the control group was 635 (±61.7); as for the fungi group, 385 (±60.4) and in the abamectin group 313 (±67.3), showing a statistically significant difference in the group treated with fungi and abamectin in comparison to the control group, with the control group having the highest averages, while the two other treated groups were overall similar. In the count of infective larvae retrieved from the pasture, the general averages presented in the control group was 2267 (±789.4), the group treated with fungi 1100 (±384.8) and the group abamectin 3115 (±1038.4), writing down that the three groups differed significantly from each other, given that the group being treated with fungi presented the lowest overall average. The fecal cultures showed a predominance of small strongyles in the three groups. It is concluded that the use of Duddingtonia flagrans and Pochonia chlamydosporia fungi is efficient in the control of gastrointestinal nematodes in horses kept on pasture, promoting a reduction in pasture infestation by infective larvae and so the degree of helminthoses.
Keywords: Anthelmintic; Helminthiasis; Macrocyclic lactones; Nematodes